2008
DOI: 10.2131/jts.33.575
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pharmacokinetic profile on the pancreatic toxicity and efficacy of tacrolimus in rats

Abstract: ABSTRACTmg/kg/day were given once daily for 8 days in the bolus intravenous injection groups. In the continuous intravenous infusion groups, tacrolimus was infused using an Alzet ® osmotic mini-pump for 9 days at the same doses. Pancreatic insulin content decreased dose-dependently in both the bolus intravenous injection -es caused by the two dosing regimens. At 0.03 mg/kg, continuous intravenous infusion did not cause glu--erance. The pharmacokinetic data indicated that continuous intravenous infusion resulte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The main measure to prevent nephrotoxicity is to reduce the systemic exposure levels and keep the local renal exposure levels to CNI and its metabolites at the lowest possible (18). We have hypothesized that the C max may be closely related to its toxicity, and the use of once-daily tacrolimus would be less toxicity by the lower C max (12). In an experimental animal model, avoidance of high peak concentrations has been associated with a reduced incidence of hyperglycemia (19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main measure to prevent nephrotoxicity is to reduce the systemic exposure levels and keep the local renal exposure levels to CNI and its metabolites at the lowest possible (18). We have hypothesized that the C max may be closely related to its toxicity, and the use of once-daily tacrolimus would be less toxicity by the lower C max (12). In an experimental animal model, avoidance of high peak concentrations has been associated with a reduced incidence of hyperglycemia (19).…”
Section: Discussionmentioning
confidence: 99%
“…A prolonged-release formulation of tacrolimus (Graceptor or Advagraf, Astellas Pharma; referred to as Tacrolimus QD) was developed to allow once-daily dosing and to have similar safety and efficacy profiles to Tacrolimus BID with the potential for improving patient's drug adherence and quality of life (10,11). Furthermore, the use of once-daily tacrolimus may decrease the toxicity of the drug by the low maximal blood concentration (C max ) (12). However, tacrolimus has a narrow therapeutic window and highly individual variable pharmacokinetic (PK) characteristics, monitoring of drug exposure is strongly recommended, but limited data are available on the kinetics of Tacrolimus QD in de novo transplanted kidney recipients (11).…”
mentioning
confidence: 99%
“…The focus on equivalence in AUC 24 was based on pre‐clinical and clinical data that showed this to be a significant variable associated with efficacy, while C max was not a significant variable. Therefore, the same efficacy could be presumed if the total daily AUC was maintained . This is discussed further in a review by Barraclough et al…”
Section: Introductionmentioning
confidence: 89%
“…Previous studies showed the efficacy of drug depends on total exposure rather than C max . (26,27). On the other hand, a study demonstrated that drug side effects may be reduced by lowering the peak blood level of drug concentration (27).…”
Section: Discussionmentioning
confidence: 99%
“…(26,27). On the other hand, a study demonstrated that drug side effects may be reduced by lowering the peak blood level of drug concentration (27). The increased exposure to prednisolone increased side effects may be apparent at low dosage (28).…”
Section: Discussionmentioning
confidence: 99%